Observational study of IAC Yokohama reporting system of breast cytology along with histopathological correlation at tertiary care hospital - Rana, Jahnavi N.; Hathila, Rasik N.; Tailor, Hemali J. (International Journal of Research in Medical Sciences, 2026)
Background: The International Academy of Cytology (IAC) Yokohama system categorizes FNAC reports into five clearly defined categories with each category is associated with an estimated Risk of Malignancy (ROM) and corresponding clinical management guidelines. The present study is undertaken to evaluate and categorise breast FNAC lesions and correlate these findings with subsequent histopathological diagnoses to assess the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and ROM of FNAC under the IAC Yokohama reporting framework. Methods: Total 322 cases of cytologically diagnosed breast lesions were included in this observational cross-sectional study at Department of Pathology, Government Medical College, Majuragate, Surat, Gujarat during the period from January 2023 to June 2024 and correlated with corresponding paraffin-embedded sections, where applicable and biopsy follow up was available. Results: ROM was highest in Category 4 and Category 5 category (100%), followed by Category 3 (60%) and Category 2 (0%). In present study, sensitivity was 100%, specificity was 96.49%, positive predictive value (PPV) was 93.55% negative predictive value (NPV) was 100% and Diagnostic Accuracy was 97.33%, evaluated by considering cases with category of Atypical (C3), Suspicious of Malignancy (C4) and Malignant (C5) as positive in cytological screening test. Conclusions: IAC Yokohama System represents a simple system that allows greater diagnostic clarity and, consequently, better communication between pathologists and treating clinicians, with clear benefits for patient management.